Evaluation of volume to area ratio to aluminum alloy microstructure - Mohd Nasuha, Ab Halim; Mohd Rashidi, Maarof; Mohamed Reza Zalani, Mohamed Suffian; Asnul Hadi, Ahmad (Semarak Ilmu Publishing, 2025)
The volume to area ratio of the cavity dimension in aluminum alloy is the foundation of this study. Afterwards, the metal casting product's hardness and grain size at various points were compared. A hardness test and optical microstructure observation were part of the experiment. The findings indicate a correlation between the microstructure and the volume to area ratio. The harder and stronger the material, the smaller the grain size and the higher the ratio.